Private investments, public values: a value-based approach to argumenting for public support to the arts - Srakar, Andrej; Čopič, Vesna (Cultural trends, 2012)
Support to private investments in culture has been subject to much attention lately due to the lack of public funds during the present economic crisis. Influenced by a neoliberal paradigm that emphasises market philosophy in the provision of public services, including arts and culture, mixed-funding economy is being acclaimed as an ideal, in that it depends on private funds to supplement public funds. It is often even claimed that private funds constitute a substitute for the lack of public support. Neoliberal cultural policy discourse, implemented through the instrumentalisation of culture, is based primarily on the use value of culture. In the present economic crisis, when all existing concepts come under question and when available empirical data show that private funding of culture is decreasing, many voices are calling for a rethinking of cultural policy. We show that private investment in culture is not unrelated to state support, and furthermore, that they are not even necessarily private, in the sense of pure market mechanisms. We suggest that they are driven by non-use values, and are therefore much more "public" than commonly thought and we provide arguments in favour of state support for the development of such mechanisms.